Local Culture of Floating Market Traders in the Pancasila Economic Values - Baseran Nor (Universitas Pendidikan Ganesha, 2025)
The transformation of local cultural values to the younger generation faces challenges due to the limited internalization of values in socio-economic practices. This study aims to explore and analyze local cultural values that develop in traders’ economic practices and examine their relevance as a medium for learning the Pancasila economic principles. This research employs a qualitative approach using an ethnographic method. The research subjects consist of traders as the main actors of economic activities, selected through the snowball sampling technique. Data were collected through in-depth interviews, participant observation, and documentation, with interview guidelines serving as the main research instrument. Data analysis was conducted through data condensation, data presentation, and drawing and verifying conclusions. The results show that traders’ economic practices reflect local cultural values aligned with the principles of the Pancasila economy, including barelaan, papadaan/bubuhan/badingsanakan, batutulungan, bakalah bamanang, ampun saorang, and honesty. These values function as guidelines for economic interaction as well as social mechanisms for maintaining solidarity and sustaining relationships among economic actors. Overall, the study concludes that local cultural values are concretely integrated into economic practices and contribute to strengthening character-based economic principles grounded in Pancasila. The findings have both theoretical and practical implications for developing learning strategies and preserving cultural values within the economic context.